High‐ and low‐dose oral immunotherapy similarly suppress pro‐allergic cytokines and basophil activation in young children. Issue 2 (18th September 2018) - Kulis, Michael; Yue, Xiaohong; Guo, Rishu; Zhang, Huamei; Orgel, Kelly; Ye, Ping; Li, Quefeng; Liu, Yutong; Kim, Edwin; Burks, Arvil Wesley; Vickery, Brian P.
Abstract: Background: Mechanisms underlying oral immunotherapy (OIT) are unclear and the effects on immune cells at varying maintenance doses are unknown. Objective: We aimed to determine the immunologic changes caused by peanut OIT in preschool aged children and determine the effect on these immune responses in groups ingesting low or high‐dose peanut OIT (300 mg or 3000 mg, respectively) as maintenance therapy. Methods: Blood was drawn at several time‐points throughout the OIT protocol and PBMCs isolated and cultured with peanut antigens. Secreted cytokines were quantified via multiplex assay, whereas Treg and peanut‐responsive CD4 T cells were studied with flow cytometry. Basophil activation assays were also conducted. Results: Th2‐, Th1‐, Th9‐ and Tr1‐type cytokines decreased over the course of OIT in groups on high‐ and low‐dose OIT. There were no significant differences detected in cytokine changes between the high‐ and low‐dose groups. The initial increase in both the number of peanut‐responsive CD4 T cells and the number of Tregs was transient and no significant differences were found between groups. Basophil activation following peanut stimulation was decreased over the course of OIT and associated with increased peanut‐IgG4/IgE ratios. No differences were found between high‐ and low‐dose groups in basophil activation at the time of desensitization or sustained unresponsiveness oral food challenges. Conclusions and Clinical Relevance: Peanut OIT leads to decreases in pro‐allergic cytokines, including IL‐5, IL‐13, and IL‐9 and decreased basophil activation. No differences in T cell or basophil responses were found between subjects on low or high‐dose maintenance OIT, which has implications for clinical dosing strategies.